A Secondary Data Analysis of Trapped and Forgotten Children in Parked Vehicles among Malaysians - J. Zakaria; N.F.A. Razak; M.S.A. Hanifah; M. Widia; W.N.R.M. Nawi; N.S. Fauzan; E.H. Sukadarin (Journal of the Society of Automotive Engineers Malaysia, 2025)
Each year, numerous children die from heatstroke and hyperthermia after being left unattended in parked vehicles. This descriptive study examines the prevalence and characteristics of such incidents in Malaysia. Secondary data were collected from local news reports and relevant government agencies, followed by a structured interview with an authority officer to validate the findings. Analysis of the data revealed that between 2012 and 2024, 17 children in Malaysia died after being left alone in vehicles, with heatstroke identified as the primary cause of death. According to the Fire and Rescue Department Malaysia, 2,520 cases of children trapped in vehicles were reported from 2012 to 2022, resulting in eight injuries and four fatalities. The interview indicated that many of these cases were not due to caregiver negligence or forgetfulness, but rather attributed to system errors, such as malfunctioning vehicle locking mechanisms. Additionally, only eight police reports were filed by caregivers or concerned individuals over the same period, suggesting significant underreporting. This study highlights the urgent need for increased public awareness, preventive strategies, and policy interventions to reduce the risk of child fatalities in parked vehicles.